Odor Mixtures in Identification Testing Using Sniffin’ Sticks: The SSomix Test - Liu, David Tianxiang; Besser, Gerold; Lang, Miriam; Sharma, Gunjan; Pablik, Eleonore; Renner, Bertold; Mueller, Christian Albert (Scientific Reports, 2020)
Clinical tests assessing olfactory performance have become indispensable for diagnosing olfactory dysfunction. As time and personnel resources are limited, it would be advantageous to have shorter protocols focusing on singular aspects of olfactory performance, such as odor identification. However, such a unidimensional approach is often inconclusive and needs further tests (and tools). Hence, new testing methods with high levels of sensitivity, specificity, and reproducibility are required for clinical practice. Here, we developed a Sniffin’ Sticks odor mixture identification test method (SSomix), with emphasis on resource efficiency and simplicity of administration. SSomix consists of mixtures of two and three odors applied onto a piece of paper using 11 out of 16 items from the original Sniffin’ Sticks identification test kit. A total of 66 healthy subjects and 22 patients with olfactory dysfunction were included in the study. SSomix showed good to excellent test-retest reliability and validity. The area under the receiver operating characteristics curves indicated good diagnostic accuracy in identifying patients with reduced and severely impaired olfactory function. SSomix was a suitable downsizing of the original kit, especially regarding resource efficiency.
CRIS-Team Scopus Importer:2020-05-29